Global change threats to migrant shorebirds - D'amico, Veronica Laura (2013)
There is growing concern about the effects global change, natural and anthropic, on the environment and organisms. Migratory shorebirds are very sensitive to these changes being reflected at both individual and population levels. The long?distance migratory flights undertaken by shorebirds between breeding and non-breeding sites, which often exceed 14000 km, require numerous metabolic adjustments, in addition to the challenges related to the foraging activities, the competition for resources, the risk of predation, the unfavorable weather conditions and the exposure to parasites and pathogens. A successful migration implies that individuals are in optimal physical condition to enable them to meet these challenges, reach nesting sites and ensure survival. Therefore, environmental perturbations, resulted from global changes, such as loss or alteration of habitat, introduced species, pollution, contamination, and increasing human activities on the sites used by birds, can affect the condition health of individuals and the phenology of migration and breeding, threatening the survival of shorebird species. This session will highlight researches on how natural and anthropogenic factors mainly, can affect the sites used by shorebird as nesting and stopover, and how these impacts can have effects on redistribution and abundance of its populations.